Standards and consumer specifications for local peanut butter - Santiago Magnolia Nepomuceno; Galvez, Flor Crisanta F. (1998.)
The study was undertaken to establish standards and specifications for local peanut butter that is acceptable to consumers. Various government agencies and institutions (Bureau of Food and Drug, Technology and Livelihood Center, Department of Agriculture and Agricultural Training Institute) were visited to gather information on existing standards. Consumer testing was conducted on three brands (one imported and two local) of peanut butter to determine what consumers consider as the desirable characteristics of this product. Color, sweetness, saltiness, taste, peanut flavor, consistency, spreadability, smoothness and overall acceptability were evaluated by 50 consumer panelists using 6-inch line scales anchored at both ends with appropriate descriptors. Results of consumer testing was subjected to analysis of variance. Information obtained from different agencies provided the definition of peanut butter and standards for texture, color, consistency, flavor and aroma and the limits for the use of additives. Consumer test results indicated that a peanut butter that is acceptable to consumers should have the following characteristics: color-slightly to medium brown, sweetness- slightly sweet, saltiness- moderately not salty, peanut flavor- slight peanut flavor, consistency- just right to slightly thick; spreadability- moderately to slightly spreadable; and smoothness-slight smooth. These characteristics were found in the local peanut samples tested.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Peanut butter